POST-DISASTER EDUCATION MANAGEMENT: AN ANALYTICAL STUDY OF PERMENDIKBUD NUMBER 33 2019 CONCERNING THE IMPLEMENTATION OF THE DISASTER SAFE EDUCATION UNIT PROGRAM - Fakhrurrozi, Hatta (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2021)
Natural disasters have an impact on educational, economic, social, political aspects, even at the religious level of the community. Some of the main factors causing many victims due to disasters are the lack of public knowledge about disasters, thus causing a lack of preparedness in anticipating the disaster. This research is a literature research, which aims to find a post-disaster management format based on Permendikbud Number 33 of 2019 concerning the Implementation of the Disaster Safe Education Unit Program. This research is motivated by the lack of socialization of the Minister of Education and Culture Number 33 of 2019 in educational institutions in Indonesia which causes schools to be unprepared in dealing with disasters. School unpreparedness further increases vulnerability to disasters. The research method uses content analysis and comparison. The results of this research analysis lead to a conclusion that school residents must be literate in disaster education as an effort to reduce disaster risk. This can be done through the following steps: 1) realizing structurally and non-structurally safe schools 2) incorporating disaster education into subject matter either through integration or separate materials, as well as intra and extra-curricular activities, 3) collaborating with the health office, BNPB , Search and Rescue, NGOs and institutions related to post-disaster management.